The Legal Security in Electronic Transactions to Protect Freedom of Speech: The Concept of Forming Legislation on Electronic Transactions - Muhammad Junaidi; Hendro Widodo; Ahmed Kheir Osman (Unissula, 2024)
The main objective of this study is to conduct a comprehensive study of the rules in criminalization which is one of the last alternatives in the law enforcement process. The Law on the Formation of Legislation in Indonesia provides Limitations of norms for violations of each legal norm formed does not violate human rights. The method used in this study was a sociological legal approach. The results of the study indicate that the norms contained in the Electronic Transaction Law in Indonesia should be a tool for law enforcers to carry out social engineering which is not a means to legalize the interests of power in Indonesia. This finding highlights the need to change the law as a constructive social engineering tool, and not as a mechanism to serve personal interests. Strengthening general provisions and clarifying norms is essential to prevent and prioritize the protection of freedoms interpreted as fundamental human rights. This study underlines the importance of aligning law enforcement with democratic values in the digital era.